Efektivitas pendekatan konseling trait and factor dengan teknik modelling untuk meningkatkan kematangan karir siswa di sekolah menengah kejuruan - Krisdiyanti, Ni Made Meliza; Dharsana, I Ketut; Suarni, Ni Ketut (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
In order to promote career maturity at SMK Negeri 3 Singaraja, this study seeks to ascertain the implementation of trait and factor advisory services using modeling methodologies. This study's methodology was exploratory. employing a random sampling strategy for sampling. Using a career maturity questionnaire, data is gathered. The Paired-Sample T-Test was employed in the data analysis technique, which made use of parametric statistical analysis and the SPSS For Windows version 20.00 software. The purpose of this research methodology is to identify the type and contributing aspects that counseling with modeling techniques has on raising student career maturity. Students in the control class and the experimental class participated in this study using a non-equivalent control group design. This investigation is. The Independent Samples t-test was utilized in this study with the assistance of SPSS Version 20 to demonstrate the significance of the Independent Samples t-test results, which were t = 4.308 > 0.05 p. The value is therefore 0.00 0.05. Thus, Ha has gained acceptance. The class XI DPIB I and II students of SMK Negeri 3 Singaraja show differences in career maturity between students who receive the trait and factor counseling approach with modeling techniques and students who do not receive the trait and factor counseling approach with modeling techniques. Additionally, it can be deduced that the effect size is 1.07 0.50 by applying the Jacob Cohen formula to the computation of the effect size. In order for Ho to accept Ha